2017
DOI: 10.4236/ojra.2017.71001
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Disorders in Chronic Non-Specific Low Back Pain in Lomé (Togo)

Abstract: Chronic non-specific low back pain has an important psychological impact. Objectives: To determine the prevalence of anxiety and depressive disorders (ADD) and factors associated to their apparition in patients suffering from chronic non-specific low back pain in rheumatological consultation in Lomé. Patients and Methods: It was a cross-sectional study, conducted from October 1 st , 2015 to 31 st March 2016. This study focused on all patients suffering from common chronic low back pain without psychiatric hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
1
1
0
1
Order By: Relevance
“…This is proven by Hung et al 27 who found that depression contributes significantly with disability among patients with CLBP. Kakpovi et al 28 and Hiyama et al 14 observed similar results in their studies that depression was significantly associated with CLBP. Hulsbusch et al 17 did not find such an association between depression and pain severity.…”
Section: Referencessupporting
confidence: 60%
“…This is proven by Hung et al 27 who found that depression contributes significantly with disability among patients with CLBP. Kakpovi et al 28 and Hiyama et al 14 observed similar results in their studies that depression was significantly associated with CLBP. Hulsbusch et al 17 did not find such an association between depression and pain severity.…”
Section: Referencessupporting
confidence: 60%
“…[12][13][14] Also, the influence of anxiety and depression is studied in chronic back pain and chronic non-specific low back pain. [15][16][17] But the relationship between neck disability due to chronic neck pain, anxiety, and depression in nonspecific neck pain has not been thoroughly investigated. Hence, as there is paucity in the literature, this study was planned to investigate the relationship between neck disability, anxiety, and depression in non-specific neck pain.…”
Section: Introductionmentioning
confidence: 99%
“…Degré d'incapacité des soignants lombalgiques (score d'Owestry) Domaines d'incapacité sévère ou extrême Nombre (%) La douleur m'empêche de me tenir debout plus d'une heure / plus d'une demi-heure 15(18,9) …”
unclassified